2019
DOI: 10.2991/jegh.k.191023.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Imaging, and Laboratory Characteristics of Adult Mexican Patients with Tuberculous Meningitis: A Retrospective Cohort Study

Abstract: Tuberculous Meningitis (TBM) is the infection of the meninges by Mycobacterium tuberculosis (Mtb) [1]. First described by Green in 1836 [2], TBM is the most common form of central nervous system tuberculosis (TB), accounting for 5-6% of extrapulmonary TB cases and for 1% of the total TB cases worldwide [1,3,4]. TBM is described as a subacute illness with a duration of symptoms that ranges 5-30 days with clinical features such as a low-grade fever, headache, and signs of meningeal irritation; in advanced stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
6
3
Order By: Relevance
“…According to TB risk factors, HIV and diabetes are the main described in the literature (13) but others such as drugs abuse, and alcoholism are important. In a Mexican cohort study in Tijuana, Baja California includes 41 TB patients, in which 51% were drug users, and 27% of alcoholics (14). This data contrasted with our series where only 10% were drug users while 52% alcoholics.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…According to TB risk factors, HIV and diabetes are the main described in the literature (13) but others such as drugs abuse, and alcoholism are important. In a Mexican cohort study in Tijuana, Baja California includes 41 TB patients, in which 51% were drug users, and 27% of alcoholics (14). This data contrasted with our series where only 10% were drug users while 52% alcoholics.…”
Section: Discussioncontrasting
confidence: 93%
“…In this series a cohort of 41 adult patients was reported. The median age was 28-years old and mortality of 19.5% (14). In a Vietnam cohort study of 1699 TBM patients, it was reported that 951 were non-HIV infected and were 748 HIV-positive, in this cohort the mortality at 9-months was 35%, and the more common predictors for increased mortality were the higher stage of Medical Research Council and the lower CSF lymphocyte cell count (22).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…CSF and urine lipoarabinomannan (LAM) are very specific yet had low sensitivity for TBM diagnosis in a cohort of mainly HIV-infected TBM patients in Zambia [15]. Circumstantial evidence may be provided by chest radiography, which identifies pulmonary abnormalities in 30–50% of patients with TBM [16,17]. Brain imaging may be improved by three-dimensional (3D) magnetization-prepared rapid gradient-echo (MP-RAGE) MRI, which has improved sensitivity due to its use of thin slices (1 mm), thereby detecting more brain lesions [18 ▪▪ ].…”
Section: Tuberculous Meningitismentioning
confidence: 99%